Boosting Anion Transport Activity of Diamidocarbazoles by Electron Withdrawing Substituents - Maslowska-Jarzyna, Krystyna; Korczak, Maria L.; Chmielewski, Michał J. (Frontiers in Chemistry, 2021)
Artificial chloride transporters have been intensely investigated in view of their potential medicinal applications. Recently, we have established 1,8-diamidocarbazoles as a versatile platform for the development of active chloride carriers. In the present contribution, we investigate the influence of various electron-withdrawing substituents in positions 3 and 6 of the carbazole core on the chloride transport activity of these anionophores. Using lucigenin assay and large unilamellar vesicles as models, the 3,6-dicyano- and 3,6-dinitro- substituted receptors were found to be highly active and perfectly deliverable chloride transporters, with EC50, 270s value as low as 22 nM for the Cl−/NO3− exchange. Mechanistic studies revealed that diamidocarbazoles form 1:1 complexes with chloride in lipid bilayers and facilitate chloride/nitrate exchange by carrier mechanism. Furthermore, owing to its increased acidity, the 3,6-dinitro- substituted receptor acts as a pH-switchable transporter, with physiologically relevant apparent pKa of 6.4.